PEMANFAATAN TAYANGAN HAFIDZ INDONESIA SEBAGAI MEDIA PEMBELAJARAN TIDAK LANGSUNG DALAM MENUMBUHKAN KECINTAAN SISWA SD TERHADAP AL-QUR’AN - Eni Rakhmawati; Hayati, Nasfa Nurul; Kasyi Fatu Rohmah; Asmala Janatul Ma’wa; Rizqy Ainurrochmah (STAI Pelabuhan Ratu, 2026)
This study aims to analyze the use of the Hafidz Indonesia program as an indirect learning medium to foster elementary school students' love of the Quran. The use of the Hafidz Indonesia program as an audiovisual medium can be a form of indirect learning outside the classroom that has the potential to foster elementary school students' love of the Quran. This study used a qualitative, descriptive approach. The subjects were 15 third-grade students at Muhammadiyah 1 Elementary School in Tegal City. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis employed an interactive model that included data reduction, data presentation, and conclusion drawing. The results showed that the Hafidz Indonesia program was utilized as an alternative learning resource outside the classroom, capable of providing an understanding of Quranic recitation, such as tajweed and makharijul huruf. Students showed positive responses in the form of admiration, focused listening, and active involvement in following the verses. The program also contributed to increasing students' love of the Quran and motivated them to memorize it. The success of its utilization was influenced by parental support and the role of teachers in providing guidance. Thus, the Hafidz Indonesia program has the potential to be an indirect learning medium in Islamic Religious Education, especially in fostering students' love for the Qur'an. Keywords: indirect learning media, Indonesian Hafidz, love of the Qur'an, elementary school students